Behavior of cacao hybrids (Theobroma cacao) to attack by Steirastoma breve (Coleoptera: Cerambycidae) - MORILLO, FRANKLIN; SÁNCHEZ, PEDRO; GIRÓN, CIRILO; VALERA, ÁNGEL; MUÑOZ, WILFREDO; GUERRA, JERÓNIMO (Revista Colombiana de Entomología, 2008)
In order to determine the behavior of cocoa hybrids to the attack of Steirastoma breve in its larval phase, the evaluation of damage intensity (DI) was carried out in a trial set up at the Padrón field experimental station in Miranda state, Venezuela. Sixty hybrid progenies were used, obtained through crossings of 27 parentals selected from among “criollo”, “trinitario” and “forastero” types. The hybrids were planted in a randomized block design with six plants and three to ten replicates, depending on the availability of material. In the first evaluation the damage produced by larvae of the insect was recorded according to the presence or absence of affected hybrids. In the second evaluation a nominal scale from one to five was used to measure the DI in 57 hybrid progenies. Highly significant differences were observed (P<0.001; Kruskal-Wallis test) in DI among hybrids in the second evaluation. Multiple comparisons of the average ranges separated the hybrids into five groups, with DI extremes from one (11 hybrids) and between three and four (five hybrids that were the most susceptible); the rest formed intermediate groups. With the exception of the materials (PV-1 x IMC-11) x OC-61 and SJU-4 x (PV-1 x IMC-11), most of the hybrids that did not present damages tended to have a genotype of Amazonian origin. The results indicate a differential behavior of the evaluated hybrids to insect attack.